The Effect of the Installation Angle of the Sky Quality Meter on the Night Sky Brightness and the Beginning of the Fajr Prayer Time - Raisal, Abu Yazid; Hidayat, Muhammad; Hermawan, Leo; Rakhmadi, Arwin Juli (Universitas Ahmad Dahlan, 2020)
Measuring the brightness of the night sky and determining the start of Fajr prayer times can be done using SQM. Observations were made at OIF UMSU with coordinates 3o 34' 55.06